A proposed teaching guide in social studies II on the concepts of "Our government, people and values" and "Our community citizenry and economic development" - Gatchalian, Violeta Briosos 1951- (1979)
This study aimed to prepare teaching guide in second year Social studies - Philippine History and Government. The conceptual-chronological approach in teaching history has been considered as a curricular arrangement of content and not a method of teaching. It is hoped that this proposed teaching guide in social studies II can be used as a model for teachers who are willing to adopt the conceptual-chronological approach.